Cooling of hypereutectic liquid Fe-C-Si: analysis of temperature - time data - Delvasto, Pedro (2011)
Two types of industrial hypereutectic Fe-C-Si alloys, with carbon saturation index as a measure of their eutecticity, SC = 1.11 and SC = 1.18, show “anomalous” behavior during their solidification processes for 3 out of 5 alloys. In order to determine their cause, behavior of their liquid cooling before solidification is analyzed through their parameters: thermal history [T-t], cooling rate [(dT/dt)L-t] and loss of heat content rate [(dQ/dt)L-t]. Simultaneous evaluation of them let us associate to the metallurgical concept of Liquid Metal Constitution (LMC) as the cause for such “anomalous” behavior, due to LMC affects the formation of phases during solidification for any type of alloys. Unetched macrostructures around thermocouple placement for the five alloys specimens solidified at cooling rates in the range of 6-8 ºC/s in precooked sand molds, demonstrate all of them are gray cast iron. Their macrostructure evidence the presence of “C”, “A”, “B”, and “D” and “E” graphite types morphologies. Total solidification times are in the range between 190 and 210 s. The origin of “anomalous” behavior observed for these alloys is concluded corresponds to superheating of liquid metal, when constant parameters: cooling rate, undercooling, type of furnace, raw materials and total solidification time, are considered through both numerical and graphical data analysis.